Spectrum and Clinical Characteristics of Symptomatic and Asymptomatic Coronavirus Disease 2019 (COVID-19) With and Without Pneumonia - Zeng, Huihui; Ma, Yiming; Zhou, Zhiguo; Liu, Wenlong; Huang, Peng; Jiang, Mingyan; Liu, Qimi; Chen, Ping; Luo, Hong; Chen, Yan (Frontiers in Medicine, 2021)
Background: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2, has become a global pandemic. Based on symptoms, COVID-19 cases can be classified as symptomatic or asymptomatic. However, there is limited information about the differences between COVID-19 patients with and without pneumonia. Our study aimed to further discuss the spectrum and clinical characteristics of symptomatic and asymptomatic COVID-19 patients with and without pneumonia. Methods: In China, all COVID-19 cases are hospitalized in designated hospitals until two continuous negative oropharyngeal swabs obtained, which allows the professional monitoring of symptoms and clinical characteristics. We stratified all COVID-19 cases in our database and evaluated clinical characteristics in different COVID-19 subgroups (symptomatic with pneumonia, symptomatic without pneumonia, asymptomatic with pneumonia, and asymptomatic without pneumonia). Results: According to symptoms and laboratory and radiologic findings, COVID-19 cases were defined as symptomatic with pneumonia, symptomatic without pneumonia, asymptomatic with pneumonia, or asymptomatic without pneumonia. There were differences in the clinical characteristics and prognosis among the four groups. Both non-invasive mechanical ventilation (18, 4.2%) and invasive mechanical ventilation (11, 2.6%) were applied in only the symptomatic with pneumonia group. Likewise, extracorporeal membrane oxygenation and continuous renal replacement therapy were applied in only the symptomatic with pneumonia group. There were no differences in viral load, the durations of viral shedding, and hospitalization among the four groups. Conclusion: We have defined a comprehensive spectrum of COVID-19 with and without pneumonia. The symptomatic with pneumonia group consumed more medical resources than the other groups, and extra caution and monitoring should be applied in this group. The asymptomatic COVID-19 group had a similar viral load and viral shedding duration as the symptomatic COVID-19 group.